Implementasi Kebijakan Program Perbaikan Gizi Masyarakat Katagori Balita Berstatus Stunting Di Kota Surabaya - Swasana, Indra Fajar; Priyanto (Soetomo Magister Ilmu Administrasi, 2024)
Reducing stunting as a program Together with the support of several teams and also members of the community participating in the success of the stunting program, whose numbers in the city of Surabaya have fallen, thanks to the hard work of all elements, a form of appreciation is given to volunteers in the context of preventing stunting in the city of Surabaya.The method used in this study is a qualitative descriptive method, where the main instrument in the research is the researcher himself. The data sources used are primary data sources and secondary data related to the empirical situation and condition of policy implementation. In this study, the authors also used interview research to obtain primary data regarding the implementation of community nutrition improvement program policies for the stunting category of toddlers in the city of Surabaya.The results of the study showed that policy standards and targets/measurements and policy objectives, Counseling or outreach to pregnant women, Provision of additional food, Activities/programs made by PMT cadres, Utilization of land that was not used by the Surabaya city government was made into productive land, planted with corn and other crops others for improving Nutrition in the city of Surabaya, Guidance and counseling to prospective husband and wife who are getting married in stunting chapter counseling, so that after the wife is pregnant, she can be well educated and One of the nutrition officers at the Lakarsantri health center in collaboration with midwives and cadres of the Posyandu Kelurahan by conducting visits to toddlers’ homes or commonly referred to as sweeping who are not present at the posyandu to measure body length, height or weight door to door. Stunting is implemented at the provincial scale and the aim of the program is to reduce stunting rates. from year to year, coordination can be carried out together with the puskesmas in the sub-district to then find out the rate of stunting and progress from implementing the Nutrition Officer program.